PREVALENCE AND RISK FACTORS OF UNDERWEIGHT FOR ADOLESCENT IN INDONESIA: A CROSS-SECTIONAL FROM GLOBAL SCHOOL-BASED STUDENT HEALTH SURVEY 2015 - Maretalinia, Maretalinia; Suryani, Dyah; Edwin, Vebby Emilia; Suyitno, Suyitno; Nilasari, Nilasari (Public Health of Indonesia, 2020)
Objective: The aim of this study was to estimate the prevalence and risk factors of underweight among adolescents in Indonesia in 2015.Methods: Cross-sectional data were analyzed from 7643 school-going adolescents from Indonesia, the "Global School-Based Student Health Survey (GSHS)" in 2015. Bodyweight was inspected by self-reported weight and height and the standards of child body mass index from WHO. The data were analyzed by univariate, bivariate, and associations with underweight were assessed using multinomial logistic regression analysis.Results: The prevalence of adolescents was found that 3002 (39.3%) were underweight in Indonesia, 2015. Sex of the adolescent who has high risk underweight was female (AOR=1.72, 95% CI=1.57-1.90) with an age range of 10-15 years old (AOR=2.37, 95% CI=2.09-2.69). Alcohol use (AOR=0.73, 95% CI=0.60-0.89) and drug use (AOR=1.82, 95% CI=1.01-3.04) were risk behavior factors for underweight among adolescents in Indonesia.Conclusion: High prevalence of underweight for adolescent were identified in Indonesia. Several correlates were identified which can help to adjust interventions from the government to the adolescent in each province.